Presence of Thrombectomy-capable Stroke Centers Within Hospital Service Areas Explains Regional Variation in the Case Fatality Rate of Acute Ischemic Stroke in Korea - Eun Hye Park; Yong Jin Gil; Chanki Kim; Beom Joon Kim; Seung-sik Hwang (Journal of Preventive Medicine and Public Health, 2021)
Objectives This study aimed to explore the status of regional variations in acute ischemic stroke (AIS) treatment and investigate the association between the presence of a thrombectomy-capable stroke center (TSC) and the case fatality rate (CFR) of AIS within hospital service areas (HSAs). Methods This observational cross-sectional study analyzed acute stroke quality assessment program data from 262 hospitals between 2013 and 2016. TSCs were defined according to the criteria of the Joint Commission. In total, 64 HSAs were identified based on the addresses of hospitals. We analyzed the effects of structure factors, process factors, and the presence of a TSC on the CFR of AIS using multivariate logistic regression. Results Among 262 hospitals, 31 hospitals met the definition of a TSC. Of the 64 HSAs, only 20 had a TSC. At hospitals, the presence of a stroke unit, the presence of stroke specialists, and the rate of endovascular thrombectomy (EVT) treatment were associated with reductions in the CFR. In HSAs, the rate of EVT treatment (odds ratio [OR], 0.98; 95% confidence interval [CI], 0.97 to 0.99) and the presence of a TSC (OR, 0.93; 95% CI, 0.88 to 0.99) significantly reduced the CFR of AIS. Conclusions The presence of a TSC within an HSA, corresponding to structure and process factors related to the quality of care, contributed significantly to lowering the CFR of AIS. The CFR also declined as the rate of treatment increased. This study highlights the importance of TSCs in the development of an acute stroke care system in Korea.